SSC (Smart Shore Connection ): Inovasi suplai kapal berbasis energi terbarukan guna mengefisiensikan emisi dan biaya pelayaran - Novandi, Faris; Amrullah, Romanda Annas; Lazim, Ahmad; Pratama, Rizki Adi; Azizah, Dhea Putriana Cahya (Jurnal Teknologi Cerdas, 2025)
In today's era, environmental quality has become a strategic global issue. Based on IQAir 2023 data, air quality in Jakarta is in a dangerous condition. In this case, sea transportation is a global contributor to Tanjung Priok Port. This is due to the use of fuel that does not comply with SOP. SSC (Smart Shore Connection) is an innovation in providing onshore electricity services to meet the needs of ship engines when docking and loading and unloading. This innovation is integrated with an electricity control application with the main electricity source coming from a hybrid of PLTS and PLTA with a switch controller mechanism. In operation, the results of the stored electricity generation are connected with a power delivery cable to the ship's engine room. Mathematically, the implementation of SSC is able to reduce emissions in the Tanjung Priok Port area by 82.71% and the value of operational cost savings is 35.9%. With this proposed innovation, it is expected to reduce air pollution in the Jakarta area so that a healthier environment is formed. In addition, ship operational costs can be reduced and will also have an impact on the welfare and smoothness of logistics in Indonesia.